2002
DOI: 10.1359/jbmr.2002.17.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Use of Type I Collagen Green Fluorescent Protein Transgenes to Identify Subpopulations of Cells at Different Stages of the Osteoblast Lineage

Abstract: Green fluorescent protein (GFP)-expressing transgenic mice were produced containing a 3.6-kilobase (kb; pOBCol3.6GFPtpz) and a 2.3-kb (pOBCol2.3GFPemd) rat type I collagen (Col1a1) promoter fragment. The 3.6-kb promoter directed strong expression of GFP messenger RNA (mRNA) to bone and isolated tail tendon and lower expression in nonosseous tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
453
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(477 citation statements)
references
References 51 publications
19
453
1
Order By: Relevance
“…Animals were kindly provided by Dr. David Rowe and Dr. Alexander Lichtler from University of Connecticut Health Center, Farmington, CT. These transgenic lines have been characterized previously, and promoter constructs have been shown to support endogenous type I collagen like tissue expression pattern (3,17). In addition, our data indicate that changes in the reporter gene closely resemble changes in mature collagen synthesis estimated by Western blot analysis of the growth media.…”
Section: Methodssupporting
confidence: 61%
“…Animals were kindly provided by Dr. David Rowe and Dr. Alexander Lichtler from University of Connecticut Health Center, Farmington, CT. These transgenic lines have been characterized previously, and promoter constructs have been shown to support endogenous type I collagen like tissue expression pattern (3,17). In addition, our data indicate that changes in the reporter gene closely resemble changes in mature collagen synthesis estimated by Western blot analysis of the growth media.…”
Section: Methodssupporting
confidence: 61%
“…To explain the cellular basis for the reduced mineralization in Psen1 +/− mice, we tracked cells of the osteoblast lineage using reporter mice that expressed GFP during early and late osteoblast progression. We crossed Psen1 +/− mice with Col3.6-GFPtpz or Col2.3-EGFP mice (24), respectively, and lineage tracked GFP + cells in adult mice in vivo, as well as ex vivo in BMSC cultures at 15 and 21 d. Previous studies with Col3.6-GFPtpz mice have shown that the 3.6 kb Col1a1 promoter is extensively expressed, in addition to skin, in osteoblasts lining the periosteal and endosteal trabecular surfaces, with weak expression in periosteal spindle-shaped preosteoblasts (24). In contrast, the 2.3-kb Col1a1 promoter marks mature osteoblasts and osteocytes in Col2.3EGFP mice (24).…”
Section: Resultsmentioning
confidence: 99%
“…We crossed Psen1 +/− mice with Col3.6-GFPtpz or Col2.3-EGFP mice (24), respectively, and lineage tracked GFP + cells in adult mice in vivo, as well as ex vivo in BMSC cultures at 15 and 21 d. Previous studies with Col3.6-GFPtpz mice have shown that the 3.6 kb Col1a1 promoter is extensively expressed, in addition to skin, in osteoblasts lining the periosteal and endosteal trabecular surfaces, with weak expression in periosteal spindle-shaped preosteoblasts (24). In contrast, the 2.3-kb Col1a1 promoter marks mature osteoblasts and osteocytes in Col2.3EGFP mice (24). In differentiating bone marrow stromal cell cultures, GFP expression is seen as early as days 7 and 14, respectively, for Col3.6-GFPtpz and Col2.3EGFP mice (24) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2.3 kb type I collagen promoter is strongly expressed in endosteal osteoblasts and osteocytes, but not in the periosteum, 10,11 whereas the 3.6 kb type I collagen promoter has been shown to be active in the periosteum. 9,12 A full AR knockout has been shown to exhibit increased bone turnover and reduced trabecular and cortical bone volume in male mice. [13][14][15][16] Further elimination of estrogen receptor a (ERa) caused an additional reduction in cortical bone mass.…”
Section: Introductionmentioning
confidence: 99%